A DNA nanosensor for monitoring ligand-induced i-motif formation. Issue 9 (18th February 2021) - Saha, Puja; Panda, Deepanjan; Paul, Raj; Dash, Jyotirmayee
Abstract : A GNP-based DNA nanosensor has been developed that identifies i-motif inducing ligands at physiological pH from a chemical library. Abstract : Herein, we present a gold nanoparticle (GNP)-based DNA nanosensor to detect the formation of an i-motif from the random coil structure by small molecules at physiological pH. The nanosensor shows a distance dependent fluorescence turn-off response in the presence of a ligand, indicating conformational changes from the C-rich single stranded DNA into an i-motif.